Psychoeducation for Relatives of Young Adults with First-Episode Psychosis: A Qualitative Exploration of Needs and Experiences. - Kuipers, S. A.; Elzinga-Hut, C. A.; Rosema, B. S.; Sanches, S.; Boertien, D.; Stavenuiter, B.; Spoelstra, S. K.; Pijnenborg, G. H. M.; Boonstra, N. (Nursing Reports, 2025)
Background/Objectives: Although psychoeducation for relatives of individuals with a first episode psychosis is important for increasing understanding of psychosis, reducing relapse rates, decreasing hospitalization duration, and improving patient functionality, there is limited research on the specific experiences and needs of relatives of patients with a first episode psychosis. This study aims to explore the experiences and needs of relatives of young adults with first-episode psychosis regarding psychoeducation, with the goal of developing tailored psychoeducation (PE) that can be delivered by nurses. Methods: This qualitative study employed a descriptive, interpretative approach with a total sample of 23 participants, including semi-structured interviews (N = 16), two dyadic interviews (N = 4) and one triadic interview (N = 3). The dyadic interviews included two relatives and two patients, while the triadic interview involved two relatives and one patient. A topic list was utilized to guide the interviews. Thematic analysis was employed to analyse the data, supported by the use of ATLAS.ti. Results: During data analysis, five key themes were identified as relevant for the development of a psychoeducational program: experiences with first-episode psychosis and psychoeducation, the content of PE (what), timing (when), exchanging experiences (how) and joint PE versus separate groups (which format). Conclusions: This study highlights valuable insights and key components for an integrated psychoeducation program, focussing on the needs and experiences of relatives, for the development of the PE program. To optimize the benefits for both parties, future research should explore the potential of offering PE sessions that accommodate both individual and combined participant formats, allowing for a design tailored to the specific needs of the participants.